The hunter killers [large type] : the extraordinary story of the first Wild Weasels, the band of maverick aviators who flew the most dangerous missions of the Vietnam War - Hampton, Dan (HarperLuxe, an imprint of HarperCollinsPublishers, 2015)
At the height of the Cold War, America's most elite aviators bravely volunteered for a covert program aimed at eliminating an impossible new threat. Half never returned. From bestselling author Dan Hampton comes one of the most extraordinary untold stories of aviation history. Vietnam, 1965: USAF Phantom jets were being blown from the sky by a mysterious weapon--a Soviet SA-2 surface-to-air missile (SAM), launched by Russian "advisors" to North Vietnam. The deadliest anti-aircraft threat in history was turning the tables of Cold War air superiority in favor of Soviet technology. Stunned and desperate, the Pentagon ordered a top-secret program called Wild Weasel I to counter the SAM problem--fast. So it came to be that a small group of maverick fighter pilots and Electronic Warfare Officers volunteered to fly behind enemy lines and into the teeth of the threat. To most it seemed a suicide mission--but they beat the door down to join. Those who survived the 50 percent casualty rate would revolutionize warfare forever. Based on unprecedented firsthand interviews with Wild Weasel veterans and previously unseen personal papers and declassified documents from both sides of the conflict, as well as Dan Hampton's own experience as a highly decorated F-16 Wild Weasel pilot, this is a cockpit-level chronicle of the remarkable band of aviators who faced the advanced Soviet missile technology head-on.--From publisher description.